The level of satisfaction and quality of E-learning in medical universities of Iran during the epidemic of COVID-19 - Mina Iravani; Maryam Beheshti Nasab; Hadis Bahmaei; Saeed Ghanbari; Zaynab Mohaghegh; Shahla Faal Siahkal (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: E-learning is web-based learning for education and training. The current global pandemic crisis created due to COVID-19 has made worldwide online learning. This study aimed to investigate the level of satisfaction and quality of E-learning in medical universities from the students' point of view during the epidemic of COVID-19 and assessing the obstacles and solutions proposed to improve the quality of E-learning. MATERIALS AND METHODS: A cross-sectional, web-based study was conducted among 400 medical university students of Iran during the epidemic of COVID-19. After getting written consent, three parts questionnaire contains demographic, user satisfaction, quality questionnaire, and three open-ended questions were distributed randomly using social media. Descriptive analysis, t-test, Chi-square, and Pearson correlation coefficient were used to achieve the objective of this study, with significance set to P < 0.05. Furthermore, three open-ended questions were reviewed qualitatively and the problems and solutions suggested by the students were reported. RESULTS: Based on the findings of the descriptive section, 277 of the respondents were girls (69%) with a mean age of 21 ± 2 years. Sixty-nine percent of students were studying in medical sciences universities and 31% were studying in Islamic Azad University. The level of satisfaction was in the upper range of low (34.0 ± 10.0); P < 0.001, and intention to reuse was moderate (23.06 ± 6.0); P = 0.064. Student's perception of quality in most domains was in the upper range of low to medium. User satisfaction, intention to reuse, the quality of knowledge, and participatory quality for evaluating online courses were significantly higher in the Azad University group than in medical universities. CONCLUSION: Given that this is the first experience in the use of E-learning in Iran, both universities have not yet fully succeeded in satisfying students and it is necessary to increase the quality of E-learning based on student suggestions.